CARACTERIZAÃÃO FÃSICO-QUÃMICA DE PROTEÃNAS PRESENTES NA MEMBRANA DE HEMÃCIAS DE PACIENTES COM ANEMIA FALCIFORME - Francisca Denyse Antonia Mendes Cruz (2013)
Sickle cell anemia (SCA) is the most common hereditary disease in Brazil and is present in about 0.1 to 0.3% of the population of African origin. This disease is caused by homozygous mutation of a single nucleotide (Glu6Val gene Hb S) that modify the function of the red cell in the body, which implies changes in membrane components and, consequently, the event sickling of red blood cells, causing vaso-occlusion. In this work we aim to identify, quantify and correlate changes in erythrocyte membrane glycoproteins associated with the framework and clinical evolution of the disease, using ion exchange chromatography (IEC) and SDS-PAGE. Were performed ion exchange chromatography on membrane proteins extracted from peripheral blood erythrocytes of 31 patients with AF. The chromatograms showed significant differences in the concentration of protein present in the membranes of red blood cells when we relate absorbance / elution range between seizure freedom and volunteers without a diagnosis of AF, depending on the clinical manifestations, patients may show differences in protein concentration. 1D SDS-PAGE revealed the presence of distinct proteins, suggesting that there are differences in the type and concentration of membrane proteins in sickle erythrocytes (both in patients without crisis as a crisis), when related to those extracted from red cells not anemic. In SDS-PAGE 2D 254 spots were identified, of which 8 spots were not identified by the program TagIdent. Most spots were distributed in the pH range 7-10, with a predominance of proteins with molecular weight less than or equal to 20 kDa. Our results suggest that analysis of sickle cells by IEC, followed by SDS-PAGE (1D and 2D), allowed differentiation and partially characterize membrane proteins of erythrocytes of patients (symptomatic and asymptomatic) with AF when related to volunteers without a diagnosis of AF . Our data reinforce the variety of biomodulation related AF, suggesting that their identification is of paramount importance for the study of adhesion between these cells sickle and the endothelium, which triggers vaso-occlusion, resulting in various symptoms.